Mentorship in Counselor Education: A Scoping Review - Gideon Litherland; Gretchen Schulthes; Edward Ewe; Kaj Kayij-Wint; Kok-Mun Ng (Teaching and Supervision in Counseling, 2023)
Mentorship has been widely lauded as meaningful for trainees in their professional development. To better understand the gaps in the scholarship of mentorship in counselor education, a scoping review was conducted to examine peer-reviewed research from 2005-2020. Results found eligible articles (n = 18) met the eligibility criteria. Implications from this study include improving conceptual rigor of mentorship outcomes in counselor education research, further investigating how underrepresented identities may benefit from mentorship, and tailoring mentorship interventions for the learning context and graduate level for counselor education students.
Keywords: mentoring; counselor education; scoping review; NASEM